Contamination of hospital surfaces by third-generation cephalosporin-resistant gram-negative bacteria in district hospitals in Mwanza, Tanzania: Urgent need for enhanced infection prevention and control - Ezekiel Gamuya; Mulki S. Salum; Beatrice Augustino Mtewele; Baraka Minja; Prisca Damiano; Conjester I. Mtemisika; Kulwa P. Mnibi; Reuben N. Abednego; Bernard C. Okamo; Vitus Silago; Stephen E. Mshana; Heike Claus; et al. (Infection Prevention in Practice)
Summary: Background: Hospital surfaces are critical reservoirs of multidrug-resistant pathogens, including third-generation cephalosporin-resistant Gram-negative bacteria (3GC-R-GNB), significantly contributing to healthcare-associated infections (HCAIs). This challenge is pronounced in low- and middle-income countries, where resource constraints limit effective infection prevention and control (IPC) measures. This study screened hospital surfaces for 3GC-R-GNB in selected District Hospitals (DHs) in Mwanza, Tanzania. Methods: This cross-sectional hospital-based study was conducted between June and July, 2023. Door handles, hand-washing sinks, patients' beds, and ward floors were sampled. Isolation of 3GC-R-GNB was done on MacConkey agar supplemented with cefotaxime (2 μg/ml). Bacterial identification was done by MALDI-TOF on Vitek MS while antimicrobial susceptibility testing was done by the Kirby-Bauer method. A multiplex PCR assay was applied for the detection of extended-spectrum beta-lactamase (ESBL) genes (blaCTX-M, blaSHV, and blaTEM). Results: A total of 892 swabs were collected from hospital surfaces, of which 243 (27.2%) were 3GC-R-GNB positive. From the 243 positive samples, 55 samples exhibited polymicrobial growth making a total of 300 bacterial isolates. The most prevalent species was Acinetobacter baumannii (26.0%, 78/300), followed by Klebsiella pneumoniae (11.0%, 33/300), Escherichia coli (8.0%, 24/300), and Leclercia adecarboxylata (7.0%, 21/300). Multiplex PCR of selected isolates (n=243) revealed that 99.6% (242/243), 93.4% (227/243), and 2.9% (7/243) 3GC-R-GNB harbored blaTEM, blaCTX-M, and blaSHV genes encoding ESBLs, respectively. Conclusion: This study reveals substantial dispersion of highly resistant Gram-negative bacteria to hospital surfaces, showing the need to prevent dispersion of such contamination and targeted hospital hygiene measures to protect patients.